The Influence Of Alfamart Retail On Profit And Loss Of Msmes In The Gegesik Area - Nur Muhamad Adam; Rusdiyana Rusdiyana; Aan Anisah (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the influence of the presence of the modern retailer Alfamart on the profit and loss conditions of micro, small, and medium enterprises (MSMEs) using a qualitative approach and observation instruments. The data used are entirely secondary data obtained from scientific journals, books, research reports, and official documents related to modern retail and MSMEs. The results of the study indicate that the presence of Alfamart generally has an impact on decreasing the turnover and profits of MSMEs, especially for small businesses that sell similar products and are located close to modern retail outlets. The decline in turnover that is not offset by a reduction in fixed costs causes a narrowing of profit margins and in many cases leads to losses and the threat of business closure. This impact is not uniform, because it is influenced by internal factors, external factors, and relational factors. The findings of the literature study also indicate a dual impact, namely Alfamart simultaneously poses a threat and an opportunity for MSMEs, depending on the adaptability of business actors and the design of policies that regulate the relationship between modern retail and MSMEs